990 ADVANCE CARE PLANS IN UK CARE HOME RESIDENTS: AN IMPLEMENTATION STUDY. (14th June 2022) - Garden, G; Usman, A; Readman, D; Storey, L; Wilkinson, L; Wilson, G; Dening, T; Gordon, A; Gladman, J
Abstract: Introduction: Research shows delivery of advance care planning (ACP) in care homes is highly acceptable, increases the proportion of residents dying in their preferred place, and reduces hospital admissions. We examined whether implementation of a service delivering ACP to care homes in Lincoln (UK) realised the research outcomes in routine practice. Method: Implementation of a service undertaking ACP in care homes was evaluated using routine data. Outcomes included proportion of care homes agreeing to participate; proportion of residents agreeing to put ACPs in place; characteristics of residents with and without ACPs, and place of death of those dying with or without ACPs. Effect on hospital admissions was examined comparing pre- and post-implementation admissions in participating homes. Results: Fifteen (63%) of 24 eligible care homes participated. ACPs were prepared for 404/516 (78%) residents. Those with ACPs were older, frailer, more cognitively impaired, and malnourished than those without. For those with ACPs (384/404; 95%), care homes were the preferred place of death. 219/248 (88%) of residents with ACPs who died did so in their care home compared to 33/49 who died without ACPs (33/49, (67%) (relative risk 1.35, 95%CI 1.1–1.6, p < 0.01). In the 15 participating homes, there were 717 hospital admissions over 360 pre-intervention care home months (mean 2.11 admissions per care home month). In the post intervention phase, there were 789 admissions over 341 care home months (mean 2.29 admissions per care home month). Conclusion: Most residents wished to have ACPs, which appeared to have influenced place of death. However, the population value of the service was limited because not all care homes participated. Hospital admissions were not reduced. Future work should aim to ensure services are universally available to residents, and to identify why reductions in hospital admissions seen in research studies may not be replicated in clinical practice.